2000
DOI: 10.1046/j.1442-2042.2000.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis caused by extracorporeal shock wave lithotripsy for bilateral renal pelvic calculi

Abstract: An elderly woman with a history of cholecystectomy and a re-operation for postoperative peritonitis underwent extracorporeal shock wave lithotripsy (ESWL) for right and left renal pelvic calculi, 11 ¥ 6 and 12 ¥ 5 mm in size, to which 2400 and 1400 shots at 20 kV were given, respectively, on the same day. During the evening after the operation, the patient started to complain of upper abdominal pain. Laboratory examination on the next day revealed elevations in blood and urine amylase levels and a diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 4 publications
0
27
1
2
Order By: Relevance
“…In this study, 513 (19.4%) developed low-grade fever, which was managed conservatively and graded into category I. A few cases of injuries to spleen and pancreas graded in category IVa have been reported in patients who received SWL to treat renal stones, although these complications are rare and manifestations vary, including death [15,16]. Stomach, duodenum, small and large bowel may be injured during SWL.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 513 (19.4%) developed low-grade fever, which was managed conservatively and graded into category I. A few cases of injuries to spleen and pancreas graded in category IVa have been reported in patients who received SWL to treat renal stones, although these complications are rare and manifestations vary, including death [15,16]. Stomach, duodenum, small and large bowel may be injured during SWL.…”
Section: Discussionmentioning
confidence: 99%
“…6 Another hypothesis is that infected urine might leak from the pelvic region and cause pancreatitis after ESWL. In our case, however, results of urinalysis and urine culture were normal.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In the published literature, many serious complications after ESWL have been reported, including pulmonary contusions, cardiac arrhythmias, gastric erosions, aortic aneurysm rupture, portal and iliac vein thrombosis, psoas abscess, retroperitoneal and brain hemorrhage, biliary obstruction, colonic and splenic injury, small bowel perforation, hepatic hematoma, and pancreatitis. [6][7][8][9][10] Only two reports of severe acute pancreatitis after ESWL exist in the published literature, and the mechanism of pancreatitis is still undetermined. 6,7 Extracorporeal shock wave lithotripsy might cause biliary pancreatitis, especially in patients with a common channel as a result of bile duct obstruction because of fragments of gallstones or common duct stones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these authors concluded that there is no clinically apparent di erence in the long-term e ect on renal function for patients with bilateral renal calculi treated with ESWL in a simultaneous versus staged fashion. Physicians caring for spinal cord injury patients should however remember that serious complications such as irreversible acute renal failure, 9 and acute pancrea- Figure 4 Following insertion of a stent in the right ureter, the ureteric calculus has been pushed in to the renal pelvis titis 10 have been reported after bilateral ESWL. An important consideration, which must be made, is that the risk of ureteric obstruction due to stone fragments must be minimal.…”
Section: Simultaneous Versus Staged Eswl Of Bilateral Renal Calculimentioning
confidence: 99%